Echocardiography in pulmonary hypertension - FRÍDL, P.; NIEDERLE, P.; WIDIMSKÝ, J.; RIEDEL, M.; JANDOVÁ, R. (Archives of Acoustics, 1984)
Echocardiographic and haemodynamic examinations were performed on 31 patients with mitral stenosis and on 49 patients with recurrent pulmonary embolism. The echocardiographic examination of the pulmonary valve was successful in 71 per cent and the measurement of right ventricular wall thickness in 95 per cent of patients. In patients with established pulmonary hypertension (mean pulmonary artery pressure 20 or more mm Hg) we observed a tendency to increased right ventricular wall thickness (r = 0.47, p < 0.001), the flattening of the e–f slope (r = 0.47, p < 0.001) and a diminished a dip (r = 0.36, p < < 0.001) on pulmonary valve echocardiograms. The higher correlation with mean pulmonary artery pressure (PAP) was found for the RPEP/RVET ratio (r = 0.55, p < 0.001) and for the right ventricular internal dimension (r = 0.65, p < 0.001). The most reliable indicator of pulmonary hypertension is the ratio of the right to the left ventricular dimension (r = 0.68, p < 0.001). Echocardiographic parameters were compared with ECG parameters of the right ventricle hypertrophy.